Extrato de bagaço de acerola: inibição de enzimas digestivas, ação antioxidante e inseticida - Marques, Tamara Rezende (2016)
Acerola (Malpighia emarginata), whose cultivation is recent in Brazil, is consumed fresh, but the big market for acerola products is generated from the clarified and concentrated juice, used as a basis in the preparation of frozen pulp, syrup for ice creams and jellies. However, the waste resulting from this processing, consisting mainly of bagasse, is discarded. Nevertheless, since they are good sources of phenolic compounds, their use in pharmaceutical, cosmetic, agrochemical and food industry can be promising. In this study, methanol and acetone extracts were prepared from acerola bagasse flour (ABF), with the objective to evaluate the methanol extract as an inhibitor source of α-amylase, α- glycosidase, lipase and trypsin inhibitors; investigate the antioxidant and hepatoprotective activities of the methanol extract against liver injury induced by CCl4 in Wistar rats; evaluate the insecticidal activity of the acetone extract against biological characteristics of Spodoptera frugiperda, as a possible alternative natural insecticide; and determine the phenolic compounds in these extracts by high-performance liquid chromatography. Acerola bagasse, obtained from the fruit processing industry, was lyophilized, homogenized using mortar and pestle and stored in hermetically sealed flasks, protected from light, in a refrigerator. For the obtention of the methanol extract, 1 g of ABF and 50 mL of 50% methanol (1:50) were used, under reflux, on a hot plate at 80 °C for 15 min. For the obtention of the acetone extract, 1 g of ABF and 10 mL of acetone:water (7:3) were used, kept at room temperature for 2 hours and then vortexed three times for 3 min. The phenolic compounds gallic acid, syringic acid, p-coumaric acid, catechin, epigallocatechin gallate, epicatechin and quercetin, were identified in the methanol extract. On the other hand, the phenolic compounds gallic acid, salicylic acid, p-coumaric acid, catechin, epigallocatechin gallate and quercetin, were identified in the acetone extract. The methanol extract was able to inhibit the digestive enzymes α-amylase and α-glucosidase, with potential to be used as an aid in the treatment of obesity and associated comorbidities. The same extract showed antioxidant and hepatoprotective activity in Wistar rats, at doses of 0.5 g and 1.0 g phenolic compounds/70 kg rat weight (RW), since the dose of 5.0 g/70 kg rat weight (RW) caused an increase in the activity of the enzyme alanine aminotransferase (ALT), reduction of superoxide dismutase (SOD) and content of serum albumin, compared to the negative control. However, the ABF acetone extract was toxic to Spodoptera frugiperda, extending the pre-pupal stage and increasing the mortality of larvae under laboratory conditions. Further studies should examine their potential use in field conditions and investigate the effect of isolated phenolic compounds identified in the ABF extract.